THE EFFECT OF INQUIRY TRAINING MODEL USE THE MEDIA PHET AGAINST SCIENCE PROCESS SKILLS AND LOGICAL THINKING SKILLS STUDENTS - Fajrul Wahdi Ginting; Nurdin Bukit (Jurnal Pendidikan Fisika, 2015)
The Purpose of The study: science process skills and logical thinking ability of students who use inquiry learning model training using PhET media; science process skills and logical thinking ability of students who use conventional learning model; and the difference science process skills and logical thinking ability of students to use learning model Inquiry Training using PhET media and conventional learning models. This research is a quasi experimental. Sample selection is done by cluster random sampling are two classes of classes VIII-E and class VIII-B, where the class VIII-E is taught by inquiry training model using media PhET and VIII-B with conventional learning model. The instrument used consisted of tests science process skills such as essay tests and tests of the ability to think logically in the form of multiple-choice tests. The data were analyzed using t test. The results showed that physics science process skills use Inquiry Training models using PhET media is different and showed better results compared with conventional learning model, and logical thinking skills students use Inquiry Training model using PhET media is different and show better results compared with conventional learning, and there is a difference between the ability to think logically and science process skills of students who use Inquiry Training model using PhET media and conventional learning models.